Potential benefits of using distributed parameter model for transmission lines in power system analysis - Ahmed, S.S.; Rajaratnam, M.; Ahmad, H.; Sidik, M.A.B. (2002)
This letter conducts load flow analysis of a five bus test system and repeats it for various sets of transmission line lengths, each with "lumped" and "distributed" models to compare the convergence, total transmission loss, and slack generation. From this comparison, we conclude that more transmission and generation capacity can be committed if a "distributed parameter" model replaces its "lumped" counterpart in such an analysis. The findings are expected to encourage the operators to take decisions through "distributed model"-based analyses so that more consumer demand can be satisfied as well as the utility's revenue substantially increased.